Effect of soil tillage on natural occurrence of fungal entomopathogens associated to Prays oleae Bern. - Oliveira, Ivo (2014)
The olive tree is one of the most important crops in Portugal, where tillage is still a normal practice performed by the growers. This work intends to evaluate the effect of tillage practices on the diversity and abundance of entomopathogenic fungi associated to Prays oleae Bern. population in the olive grove ecosystem. In order to achieve this, three tilled and three non-tilled groves were sampled for P. oleae larvae and pupae, during two consecutive years. The fungi were isolated from diseased larvae and pupae and identified by rDNA sequencing. One hundred and twenty isolates of fungi described as entomopathogenic were found, belonging to 8 different species. The most abundant species were Beauveria bassiana (60%), Cladosporium cladosporioides (18%) and Cladosporium oxysporum (14%). Olive groves under no-till system showed higher occurrence (2.7%), diversity (7 species) and abundance (65 isolates) of entomopathogenic fungi than tilled system (2.3%, 4 species and 55 isolates). Although these differences were found to be not significant, the results suggested that no-tilled olive groves with natural vegetation presented the most suitable conditions to increase the probability of P. oleae infection by entomopathogenic fungi. The highest number of exclusive species found in non-tilled groves (4 species) when compared to tilled ones (1 species) also reinforce this fact and indicated that vegetation cover may act as a reservoir for fungal species.